A systematic review of the organizational learning and performance literature - Martínez Aragón, Cynthia Lizeth (Vision de futuro, 2023)
Organizations from all sectors are in a constant struggle to survive and face changes in the globalized and complex environment. Where variables related to human resources that improve performance become relevant to adapt. Under this scenario, the purpose of this document is to identify the relationship between organizational learning and performance, through a systematic review of the literature where selection and inclusion criteria were established, as well as a research strategy. Among the primary findings, it stands out that countries belonging to Asia have been more focused on these issues, since most of the articles reviewed come from there and most of them have a quantitative approach. Furthermore, some researches added variables such as knowledge management, innovation, transformational leadership, among others. It was concluded that these are important subjects, which have been studied very little, and that the qualitative and mixed approach were studied to a lower extent. Therefore, an investigation of both variables has the potential to be innovative and interesting for academy, as well as for entrepreneurs and managers who wish to increase performance.